PENGARUH BULAN PERDAGANGAN TERHADAP RETURN SAHAM : PENGUJIAN JANUARY EFFECT DI INDEKS HARGA SAHAM LIQUIDITY 45 (Studi pada perusahaan yang bergerak di bidang keuangan perbankan yang tercatat di LQ45 selama periode 2004-2012) - Mardhiyah, Siti; Herawati, Juni (Jurnal Ilmiah Mahasiswa FEB, 2013)
Investors need to be aware of information and other factors that are always changing every second to make a decision about theirstock . This study aimed to investigate the effect of months of trading on stock returns in the banking LQ45 and active during the period 2004-2012 . Some studies reveal that the tendency is always positive returns during the month of January ( January effect ) . But some research suggests that the January effect only occurs in certain stocks and the some countries. Researchmetodeto determine the trend of positive returns each January using descriptive analysis . Descriptive analysis illustrates the average stock return . Proceed with the testing process using the homogeneity test , normality test , and Kruskal Wallis.Uji normality showed that the data were sampled data that does not have a normal distribution , so as to test the hypothesis have touse a non parametrik. Hypothesis testthatusing Kruskal Wallis test showed that there are differences in returns in January with theother months.Keywords :Â  January effect, Return Saham, Bulan Perdagangan,saham perbankan,Â  indeks harga saham LQ45